Constraints definition and application optimization based on geometric analysis of the frequency measurement method by pulse coincidence. (October 2018) - Avalos-Gonzalez, Daniel; Sergiyenko, Oleg; Hernandez-Balbuena, Daniel; Tyrsa, Vera; Kartashov, Vladimir; Rivas-Lopez, Moises; Rodriguez-Quiñonez, Julio; Flores-Fuentes, Wendy; Murrieta-Rico, Fabian N.
Highlights: Geometric analysis of the frequency measurement method by pulse coincidence. Quantity of coincidences in a measurement. Relation between pulse coincidence method and Euclid's algorithm. Abstract: In this paper a new and more efficient algorithm for frequency measurement using pulse coincidence is introduced. This novel approach reduces 42% the measurement time while the same accuracy is maintained. The simplicity of the algorithm proposed in this work is compared with other similar methods that are related with analog to digital converters and the discrete Fourier transform. Geometric analysis was performed to the signals involved in the frequency measurement process in order to obtain mathematical parameters for the correct implementation of this new method. Simulated signals and generated signals from a homemade system were used to validate this method's scope.